Field Diagnosis of Citrus Root Weevil Damage - Stephen H. Futch; Clayton W. McCoy; James H. Graham; Larry W. Duncan; Herbert N. Nigg (EDIS)
Root weevils infest citrus groves throughout the citrus growing regions of Florida. Among the eight weevil species that have been identified in Florida citrus groves, five have some potential to cause economic problems for nurserymen and commercial growers. The most important weevil species are Diaprepes root weevil (Diaprepes abbreviatus), southern blue-green citrus root weevil (Pachnaeus litus), and the blue-green citrus root weevil (Pachnaeus opalus). The little leaf notcher (Artipus floridanus) and Fuller rose beetle (Asynonychus godmani) are of less concern, but may be locally important (Fig. 1). This paper will deal with Diaprepes and the blue-green root weevils because they are of major economic importance and frequently occur in citrus groves. This document is HS-1014, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date May 2005.